Intellectual Component of Human Language Model in the Russian and Baltic Languages (based on Material of Phraseological Units of the Russian, Latvian and Lithuanian Languages) - Stoikova, Tatyana (Slavistica Vilnensis, 2025)
The article considers the intellectual component of the Russian and Baltic human language model (HLM) based on the material of phraseologisms. The intellectual component is characterized by somatic phraseological units (PhU) with key components correlated in Russian and Baltic languages: Rus. голова, мозг (мозги), ум, разум, рассудок / Latv. galva, smadzenes, prāts, saprāts / Lithuan. galva, smegenys, protas, omuo. In the semantics of the analyzed PhU, the following aspects of human intellectual activity are updated: normal / abnormal intellectual state; judiciousness, common sense / imprudence; good / poor mental capacity; a “container” of thoughts and quantitative indicators of mind and knowledge; memory abilities, normal thought activity / mental disorders. A comparative analysis of the semantics of Russian and Baltic PhU revealed common typological features of the compared HLM. Interlanguage Russian and Baltic correspondences in most cases are full equivalents, that is, identical in structure, composition of components and figurative bases, less often they are partial, that is, such in which there is a variation in components and grammatical structure. The identity of figurative foundations is a demonstration of the commonality of cultural connotations which, in turn, testifies to the commonality of many cultural attitudes of Russians and Balts. Apparently, interlanguage Russian, Latvian and Lithuanian equivalents go back to identical prototypes that developed into corresponding PhU under the combined action of universal (for all three ethnic groups) linguistic and extralinguistic factors, and this confirms the hypothesis of interlanguage phraseological parallelism, especially in the case of somatic phraseologisms.